(untitled) (Revista de História da UEG (REVHIST), 2020)
Abstract: This article discusses the repercussion of Darwinian and Darwinism ideas in the Brazilian Catholic press of the second half of the 19th century, emphasizing the anti-Darwinist debate advocated by ecclesiastical agents. We will to highlight beyond the texts the social and cultural contexts in which Darwinism was received, demonstrating its adaptations as internal needs. One of the main characteristics of the press in the nineteenth century was to educate and inform its reading public, thus, this study assists in the understanding of Darwinism that was informed and sought to form in its readers. We believe that the Brazilian clergy, such as the secular intellectuals, was aware of the main innovation that animate the international scientific field, however, had a partial knowledge of evolutionary ideas, especially related to Darwinian theories. Keywords: Anti-Darwinism. Charles Darwin. Catholic press.